METHODOLOGY OF TEACHING INFORMATION COMMUNICATION TECHNOLOGIES AND SYSTEMS IN THE ECONOMY IN HIGHER EDUCATION INSTITUTIONS BASED ON WEB TECHNOLOGIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the methodology of teaching Information and Communication Technologies (ICT) and systems in economics at higher education institutions using web-based technologies. The study analyzes the implementation of digital infrastructure, distance learning tools, online platforms, and interactive teaching methods in economic education. Special attention is given to competency-based assessment systems, student-centered learning strategies, and the integration of practical tasks related to real-world economic scenarios.